Numerical evaluation of hydrodynamic characteristics of planing hulls by using a hybrid method - Kahramanoglu, Emre; Pennino, Silvia; Yilmaz, Huseyin (SAGE PUBLICATIONS LTD, 2021)
The hydrodynamic characteristics of the planing hulls in particular at the planing regime are completely different from the conventional hull forms and the determination of these characteristics is more complicated. In the present study, calm water hydrodynamic characteristics of planing hulls are investigated using a hybrid method. The hybrid method combines the dynamic trim and sinkage from the Zarnick approach with the Savitsky method in order to calculate the total resistance of the planing hull. Since the obtained dynamic trim and sinkage values by using the original Zarnick approach are not in good agreement with experimental data, an improvement is applied to the hybrid method using a reduction function proposed by Garme. The numerical results obtained by the hybrid and improved hybrid method are compared with each other and available experimental data. The results indicate that the improved hybrid method gives better results compared to the hybrid method, especially for the dynamic trim and resistance. Although the results have some discrepancies with experimental data in terms of resistance, trim and sinkage, the improved hybrid method becomes appealing particularly for the preliminary design stage of the planing hulls.
Keywords: 2D+T method; planing hull; potential based solver; Engineering